Identification of sRNAs expressed by the human pathogen Neisseria gonorrhoeae under disparate growth conditions - McClure, Ryan; Tjaden, Brian; Genco, Caroline (Frontiers in Microbiology, 2014)
In the last several years, bacterial gene regulation via small RNAs (sRNAs) has been recognized as an important mechanism controlling expression of essential proteins that are critical to bacterial growth and metabolism. Technologies such as RNA-seq are rapidly expanding the field of sRNAs and are enabling a global view of the “sRNAome” of several bacterial species. While numerous sRNAs have been identified in a variety of both Gram-negative and Gram-positive bacteria, only a very small number have been fully characterized in the human pathogen Neisseria gonorrhoeae, the etiological agent of the STD gonorrhea. Here we present the first analysis of N. gonorrhoeae specifically focused on the identification of sRNAs through RNA-seq analysis of the organism cultured under different in vitro growth conditions. Using a new computational program, Rockhopper, to analyze prokaryotic RNA-seq data obtained from N. gonorrhoeae we identified several putative sRNAs and confirmed their expression and size through Northern blot analysis. In addition, RNA was collected from four different growth conditions (iron replete and deplete, as well as with and without co-culture with human endocervical cells). Many of the putative sRNAs identified shoed varying expression levels relative to the different growth conditions examine or were detected only under certain conditions but not others. Comparisons of identified sRNAs with the regulatory pattern of putative mRNA targets revealed possible functional roles for these sRNAs. These studies are the first to carry out a global analysis of N. gonorrhoeae specifically focused on sRNAs and show that RNA-mediated regulation may be an important mechanism of gene control in this human pathogen.